Redundant potassium transporter systems guarantee the survival of Enterococcus faecalis under stress conditions - Acciarri, Giuliana; Gizzi, Fernán O.; Torres Manno, Mariano A.; Stülke, Jörg; Espariz, Martín; Blancato, Víctor S.; Magni, Christian (Frontiers in Microbiology, 2023)
Enterococcus is able to grow in media at pH from 5.0 to 9.0 and a high concen-tration of NaCl (8%). The ability to respond to these extreme conditions requires the rapid movement of three critical ions: proton (H+), sodium (Na+), and potassium (K+). The activity of the proton F0F1 ATPase and the sodium Na+ V0V1 type ATPase under acidic or alkaline conditions, respectively, is well established in these microorganisms. Related to K+ uptake in Enterococcus, KtrI and KtrII were described in the model mi-croorganism E. hirae, which were associated with growth in acidic and alkaline condi-tions, respectively. In E. faecalis, the presence of the Kdp (potassium ATPase) system was early established. However, the homeostasis of potassium in this microorganism is not completely explored. In this study, we demonstrate that Kup and KimA are high-affinity potassium transporters, and the inactivation of these genes in E. faecalis JH2-2 (Kdp deficient strain) had no effect on the growth parameters. However, in KtrA defec-tive strains (ΔktrA, ΔkupΔktrA) an impaired growth was observed under stress condi-tions, which was restored to wild type levels by external addition of K+ ions. Among the multiplicity of potassium transporters identify in the genus Enterococcus, Ktr (KtrAB and KtrAD), Kup and KimA are present and may contribute to the particular resistance of these microorganisms to different stress conditions and may contribute to the particular resistance of these microorganisms to different stress conditions. In addi-tion, we found that the presence of the Kdp system in E. faecalis is strain-dependent, and this transporter is enriched in strains of clinical origin as compared to environmental, commensal, or food isolates.